Literasi Informasi Penyuluh Pertanian di Kabupaten Cianjur - Rasmira Rasmira (Jurnal Penyuluhan, 2019)
In the information overload, agricultural extension agents as agents of agricultural development need to have information literacy skills because most of their main tasks and functions are related to the activities of collecting, processing and disseminating agricultural information. This study aims to 1) identify information literacy among extension workers in Cianjur Regency2) analyze the factors that are related to information literacy among extension workers in Cianjur Regency. The study sample was 80 extension workers in Cianjur Regency. The method of analysis uses descriptive statistics and inferential statistics using Spearman Rank correlation to analyze relationships between variables. The results showed that the information literacy level of agricultural extension workers was classified as middle especially in storing and retrieving information, using information effectively and ethically, and communicating knowledge. Extension agents have a high ability in terms of recognizing the information needed, finding and evaluating it. Two factors that are significantly related to information literacy are characteristics of extension agents (age, formal education level, working life) and accessibility of communication media (ease of access and variety of media uses).